Career termination of Portuguese elite football players: Comparison between the last three decades - Carapinheira, A.; Mendes, P.; Guedes Carvalho, P.; Torregrossa, M.; Travassos, B. (Sports, 2018)
The aim of this study was to explore the process of career termination of elite soccer players, comparing the quality and the resources to support career termination over the last three decades. To this end, was developed a questionnaire defined by four sections: (a) biographical data, (b) athletic career, (c) quality of career termination and (d) available resources at the moment of career termination. Ninety male former elite Portuguese soccer players participated in this study. The results highlighted a decrease in the length of athletic career as football players and an increase in the number of years as youth players over the last 30 years. The results also revealed that the quality of career termination was difficult. The analysis of resources for career termination revealed an increase in a high level of education over the years. Despite the evolution in the level athletes` education in the last three decades, the athletic career termination remained difficult and it was reported that they did not plan their career termination. In line with previous studies, the results highlight that the lack of plans for career termination is one of the most important factors that constrain the quality of career transition